Workshop Clinic on Evaluation Practices - Sette, Cristina (CGIAR Challenge Program on Water and Food, 2012)
On 9 January 2012, a workshop clinic was held at the International Water Management Institute (IWMI) office in Accra, Ghana, organized by Dr. Olufunke Cofie (Challenge Program on Water and Food -‐ CPWF, of the CGIAR) and Ms Cristina Sette (Institutional Learning and Change Initiative -‐ ILAC, of the CGIAR), and led by Prof. Patricia Rogers, from the Royal Melbourne Institute of Technology -‐ RMIT, a well known professional in the field of program theory and evaluation. The results of the workshop were very positive as there was great engagement and participation from the 13 professionals present. The 3 hour workshop was structured in 7 sessions: (1) introduction, (2) what is good evaluation, (3) presentation on the CPWF in the Voltabasin, (4) professional practice fishbowl, (5) reflection on the fishbowl exercise, (6) next steps, and (7) a short presentation on the BetterEvaluation project.